To Commemorate the 200th Anniversary of Thomas Robert Malthus Book “An Essay on Population” - Kasnauskienė, Gindra (Ekonomika, 1998)
T. R. Malthus, still today best known name in the field of population, stated issues and dilemmas around which research and controversy have revolved since the first “Essay on Population” was published in 1798. In one sentence, the Malthusian principle is that population tends to grow until it presses against the means of subsistence. He was not the first to propound the theory that population tends to increase proportionately faster than the supply of food. But the style of essay and many evidences presented in the latest five editions undoubtedly contributed to the impact of the work on a community. There were not only the observation of tendencies but also reference to the bad structure of society and unfavourable distribution of wealth. Malthus bas been widely read, but be bas also been widely misquoted. The most important Malthus achievement was to show that population studies can be examined and analysed empirically and discussed on a rational basis.